Single-step process to improve the mechanical properties of carbon nanotube yarn - Evora, Maria Cecilia; Lu, Xinyi; Hiremath, Nitilaksha; Kang, Nam-Goo; Hong, Kunlun; Uribe, Roberto; Bhat, Gajanan; Mays, Jimmy (Beilstein Journal of Nanotechnology, 2018)
Carbon nanotube (CNT) yarns exhibit low tensile strength compared to conventional high-performance carbon fibers due to the facile sliding of CNTs past one another. Electron beam (e-beam) irradiation was employed for in a single-step surface modification of CNTs to improve the mechanical properties of this material. To this end, CNT yarns were simultaneously functionalized and crosslinked using acrylic acid (AA) and acrylonitrile (AN) in an e-beam irradiation process. The chemical modification of CNT yarns was confirmed by X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and scanning electron microscopy (SEM). The best improvement in mechanical properties was achieved on a sample treated with an aqueous solution of AA and subsequent irradiation. CNT yarn treatment with AA enhanced the strength (444.5 ± 68.4 MPa) by more than 75% and the modulus (21.5 ± 0.6 GPa) by more than 144% as compared to untreated CNT yarn (strength 251 ± 26.5 MPa and modulus 8.8 ± 1.2 GPa).
Keywords: carbon nanotube yarns; crosslinking; electron beam; grafting